Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Assessing the intensity of Late Quaternary humid phases in the Nefud Desert, northern Arabia - Richard Clark‐Wilson; Simon J. Armitage; Ian Candy; Paul S. Breeze; Nick A. Drake; Huw S. Groucutt; Abdullah M. Alsharekh; Faisal Al‐Jibreen; Michael D. Petraglia; David B. Ryves (Journal of Quaternary Science, 2026)
The climate history of the major dryland zones of the world, such as the Saharo–Arabian Desert belt, plays a key role in the dispersal of early humans through these intermittently inhospitable regions. Here, we assess the relative intensity of Late Quaternary humid phases in northern Arabia through lithological, geochemical, palaeoecological and geochronological analysis of three sediment sequences in the Nefud Desert. Two sequences are marl beds that accumulated in perennial, groundwater‐fed lake systems during two distinct humid phases that occurred in MIS 5e and MIS 5a. The third records sediment accumulation within an ephemeral lake system during the terminal Pleistocene/early Holocene. The altitude of the two MIS 5 deposits indicates that the water table must have reached altitudes of >929 m ASL (MIS 5e) and >922 m ASL (MIS 5a). In contrast, the sedimentary characteristics of the early Holocene sequence imply that, during this interval, the water table was

Mechanical site preparation treatment and species effects on carbon pools in 12-year-old American sycamore [Platanus occidentalis L.] and willow oak [Quercus phellos L.] riparian plantations, Virginia Piedmont, USA - Drake H. Lynn; W. Michael Aust; David R. Carter; P. Corey Green; John R. Seiler (New Forests, 2025)
Restoration of riparian forests can improve water quality and wildlife habitat and also sequester carbon. Unfortunately, failures of riparian restoration efforts are common due to planting mortality. Selection of well-suited species, dense planting and use of mechanical soil site preparations may potentially enhance wetland restoration plantings. Carbon valuation of forestland is increasing and additional research is needed to determine rates and pools of carbon accumulation in riparian areas. We evaluated the effects of four soil mechanical site preparation treatments (bedding, disking, pit and mounding, and ripping) and species selection (American sycamore [ Platanus occidentalis L.] and willow oak, [ Quercus phellos L.] on survival, growth and carbon storage across multiple pools: planted trees, herbaceous vegetation, fine roots, organic soil (litter) horizons, and the mineral soil. At 12 years, species selection was more important to carbon storage than site preparation. American sycamore was well-suited to the site and had better survival than willow oak (64% vs. 42% survival). American sycamore also stored more carbon across all site preparation methods than willow oak. Measured carbon storage averaged 74.8 Mg ha −1 for American sycamore treatments and 63.1 Mg ha −1 for willow oak treatments. The densely planted treatments established forests even in higher mortality willow oak plots. Results indicate that appropriate species planted at high densities may be used to enhance forest stand establishment and carbon storage in similar riparian restorations.

Late Quaternary inundation and desiccation of Megalake Chad traced in dust records from the Equatorial Atlantic Ocean - Anya J. Crocker; Christopher W. Kinsley; Amy M. Jewell; Paul S. Breeze; Nicholas A. Drake; David McGee; Charles S. Bristow; Katie Manning; Claudia Di Biagio; Paola Formenti; William R.C. Burton; Annie L. Murray; et al. (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Assessing the impact of homeowner associations’ pro-environmental codes, covenants, and restrictions on member yards - Madeline F. Carr; Daniel Boyd Kramer; David Drake (Landscape and Urban Planning, 2025)

Effects of burning on vegetation, soil physicochemistry and prokaryotic microbial communities in surface and subsurface peat - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Science of The Total Environment, 2024)

Patterns in tree squirrel co-occurrence vary with responses to local land cover in US cities - Rachel N. Larson; Heather A. Sander; Mason Fidino; Julia L. Angstmann; Sheryl Hayes Hursh; Seth B. Magle; Katrina Moore; Carmen M. Salsbury; Theodore Stankowich; Katherine Tombs; Lauren Barczak; Alyssa M. Davidge; et al. (Urban Ecosystems, 2024)

Changes in nitrogen functional genes and microbial populations in soil profiles of a peatland under different burning regimes - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Applied Soil Ecology, 2024)

Local socioeconomic factors predict urban forest structure and composition across neighborhoods in Syracuse, NY (USA) - Jordan Jessamy; John E. Drake; David J. Nowak; John C. Stella (Landscape and Urban Planning, 2024)

Holistic valuation of non-native species requires broadening the tent - Emily M.X. Reed; Todd Schenk; Bryan L. Brown; Haldre Rogers; David C. Haak; Joseph C. Drake; Jacob N. Barney (Trends in Ecology & Evolution, 2023)

Reproductive phenology and behaviour of endangered redside dace ( Clinostomus elongatus ) in urban streams - Ashley M. Watt; D. Andrew R. Drake; David Lawrie; Trevor E. Pitcher (Journal of Fish Biology, 2023)
Investigation of the reproductive phenology and spawning behaviour of imperilled species in relation to environmental variability is needed to understand a critical component of species life history. In this study, we used redside dace ( Clinostomus elongatus ), a freshwater leuciscid listed as Endangered under Canada's Species at Risk Act , to model spawning phenology and make predictions about spawning initiation using historical and climate change projected thermal cues (measured as cumulative growing degree days), and provide an ethological description of spawning behaviour. Logistic regression models applied to 4 years of average daily stream water temperature data and field behavioural observations of the onset of spawning activity indicated a 50% probability of spawning initiation when cumulative growing degree days reached 214°C days and a 95% probability of spawning initiation at 288°C days. Using two climate change scenarios ( i.e. , a mid‐century 1.6°C increase and an end of century 3.6°C increase), spawning initiation was predicted to advance 3 days by the year 2050 and 7 days by the year 2100. Underwater video cameras placed at two sites within an urban stream captured 73 unique spawning events revealing that redside dace spawn in pairs as well as in dense, tightly packed groups (more than 20 individuals). Moreover, there is evidence of redside dace having a polygynandrous mating system, as female redside dace spawned with multiple males in 45.2% of the total spawning events recorded. Taken together, this study provides important insights into redside dace spawning initiation and behaviour, key life‐history traits having conservation implications for future reproductive success and, ultimately, population dynamics.

An urban cast of characters: Landscape use and cover influencing mammal occupancy in an American midwestern city - Sheryl Hayes Hursh; Javan M. Bauder; Mason Fidino; David Drake (Landscape and Urban Planning, 2023)

Multiscale drivers of amphibian community occupancy in urban ponds - Erin L. Sauer; Jennyffer Cruz; Erin Crone; Catherine Lewis; Ethan Plumier; Blake Cwynar; David Drake; Bradley M. Herrick; Daniel L. Preston (Urban Ecosystems, 2022)

Effects of invasive jumping worms (Amynthas spp.) on microhabitat and trophic interactions of native herpetofauna - Erin R. Crone; Erin L. Sauer; Bradley M. Herrick; David Drake; Daniel L. Preston (Biological Invasions, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mechanisms underlying lack of functional compensation by insect grazers after tadpole declines in a Neotropical stream - Thomas R. Barnum; John Timothy Wootton; Rebecca J. Bixby; John M. Drake; David Murray‐Stoker; Checo Colón‐Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; et al. (Limnology and Oceanography, 2022)
Resilience of ecosystems to the sudden decline of large‐bodied species is dependent on characteristics of surviving guild members. However, that response may also be mediated by local habitat conditions. Here, we examine the mechanisms behind the observed lack of functional compensation in the algal‐grazing guild by insect grazers following the decline of tadpole grazers in a forested Panamanian stream. We examined: (1) shifts to the individual size distribution of insect grazers between pre‐ and post‐tadpole declines in pool and riffle habitats; (2) tadpole and insect preferences for small‐, medium‐, and large‐sized diatoms; and (3) a causal explanation for why insects did not functionally compensate for tadpole declines. The size distribution of insect grazers following tadpole declines differed between habitats, becoming uniform in pools and more right skewed toward a smaller size class in riffles. In both habitats, tadpoles selectively consumed medium‐sized diatoms but avoided the largest‐sized diatoms. In contrast, grazing insects selectively consumed small‐sized diatoms, but switched to medium‐sized diatoms after tadpole declines. Tadpole declines led to the loss of the strongest interactions between consumers and diatoms. Smaller‐bodied grazing insects could not duplicate these interactions, even with a shift in resource use, providing an explanation for the lack of functional compensation. Furthermore, tadpole declines led to different community structures in each habitat indicating that local habitat conditions mediated the response of surviving guild members. This suggests that the sudden decline of a large‐bodied species does not lead to a singular outcome for the surviving community.

Derivation of stable embryonic stem cell-like, but transcriptionally heterogenous, induced pluripotent stem cells from non-permissive mouse strains - Tiffany A. Garbutt; Kranti Konganti; Thomas Konneker; Andrew Hillhouse; Drake Phelps; Alexis Jones; David Aylor; David W. Threadgill (Mammalian Genome, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Land‐use controls on carbon biogeochemistry in lowland streams of the Congo Basin - Travis W. Drake; David C. Podgorski; Bienvenu Dinga; Jeffrey P. Chanton; Johan Six; Robert G. M. Spencer (Global Change Biology, 2020)
The flux and composition of carbon (C) from land to rivers represents a critical component of the global C cycle as well as a powerful integrator of landscape‐level processes. In the Congo Basin, an expansive network of streams and rivers transport and cycle terrigenous C sourced from the largest swathe of pristine tropical forest on Earth. Increasing rates of deforestation and conversion to agriculture in the Basin are altering the current regime of terrestrial‐to‐aquatic biogeochemical cycling of C. To investigate the role of deforestation on dissolved organic and inorganic C (DOC and DIC, respectively) biogeochemistry in the Congo Basin, six lowland streams that drain catchments of varying forest proportion (12%–77%) were sampled monthly for 1 year. Annual mean concentrations of DOC exhibited an asymptotic response to forest loss, while DIC concentrations increased continuously with forest loss. The isotopic signature of DIC became significantly more enriched with deforestation, indicating a shift in source and processes controlling DIC production. The composition of dissolved organic matter (DOM), as revealed by ultra‐high‐resolution mass spectrometry, indicated that deforested catchments export relatively more aliphatic and heteroatomic DOM sourced from microbial biomass in soils. The DOM compositional results imply that DOM from the deforested sites is more biolabile than DOM from the forest, consistent with the corresponding elevated stream CO 2 concentrations. In short, forest loss results in significant and comprehensive shifts in the C biogeochemistry of the associated streams. It is apparent that land‐use conversion has the potential to dramatically affect the C cycle in the Congo Basin by reducing the downstream flux of stable, vascular‐plant derived DOC while increasing the transfer of biolabile soil C to the atmosphere.

An extreme heatwave enhanced the xanthophyll de-epoxidation state in leaves of Eucalyptus trees grown in the field - Namraj Dhami; John E. Drake; Mark G. Tjoelker; David T. Tissue; Christopher I. Cazzonelli (Physiology and Molecular Biology of Plants, 2020)

Determining the Sources of Variance in the Preparation of Analytical Standards for Chromatographic Analysis of a Lyophilized Peptide Drug Substance by Nested ANOVA Statistical Analysis - Paul L. Walsh; John Lena; Jennifer Drake; David Lavrich (AAPS PharmSciTech, 2020)

The Influence of Electrostatic Controls on MDI Size Distribution Measurements - Stephen W. Stein; Jack Rasmussen; Sheila Walls; David W. Schultz; Claire Oakley; James B. Drake (AAPS PharmSciTech, 2019)

Range size and growth temperature influence Eucalyptus species responses to an experimental heatwave - Michael J. Aspinwall; Sebastian Pfautsch; Mark G. Tjoelker; Angelica Vårhammar; Malcolm Possell; John E. Drake; Peter B. Reich; David T. Tissue; Owen K. Atkin; Paul D. Rymer; Siobhan Dennison; Steven C. Van Sluyter (Global Change Biology, 2019)
Understanding forest tree responses to climate warming and heatwaves is important for predicting changes in tree species diversity, forest C uptake, and vegetation–climate interactions. Yet, tree species differences in heatwave tolerance and their plasticity to growth temperature remain poorly understood. In this study, populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an equivalent experimental heatwave. We tested whether the species with large and small range sizes differed in heatwave tolerance, and whether trees grown under warmer temperatures were more tolerant of heatwave conditions than trees grown under cooler temperatures. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. In general, species that showed less tissue damage maintained higher stomatal conductance, lower leaf temperatures, larger increases in isoprene emissions, and less photosynthetic inhibition than species that showed more damage. Species exhibiting more severe visible damage had larger increases in heat shock proteins (HSPs) and respiratory thermotolerance ( T max ). Thus, across species, increases in HSPs and T max were positively correlated, but inversely related to increases in isoprene emissions. Integration of leaf gas‐exchange, isoprene emissions, proteomics, and respiratory thermotolerance measurements provided new insight into mechanisms underlying variability in tree species heatwave tolerance. Importantly, warm‐grown seedlings were, surprisingly, more susceptible to heatwave damage than cool‐grown seedlings, which could be associated with reduced enzyme concentrations in leaves. We conclude that species with restricted range sizes, along with trees growing under climate warming, may be more vulnerable to heatwaves of the future.

The prevalence of parasitic pea crab Afropinnotheres monodi in mussels depending on the degree of exposure of habitats: implications for mussel culture - Pilar Perez-Miguel; Jose Cuesta; Enrique González-Ortegón; David Roque; Pilar Drake (Frontiers in Marine Science, 2019)

Trees tolerate an extreme heatwave via sustained transpirational cooling and increased leaf thermal tolerance - John E. Drake; Mark G. Tjoelker; Angelica Vårhammar; Belinda E. Medlyn; Peter B. Reich; Andrea Leigh; Sebastian Pfautsch; Chris J. Blackman; Rosana López; Michael J. Aspinwall; Kristine Y. Crous; Remko A. Duursma; et al. (Global Change Biology, 2018)
Heatwaves are likely to increase in frequency and intensity with climate change, which may impair tree function and forest C uptake. However, we have little information regarding the impact of extreme heatwaves on the physiological performance of large trees in the field. Here, we grew Eucalyptus parramattensis trees for 1 year with experimental warming (+3°C) in a field setting, until they were greater than 6 m tall. We withheld irrigation for 1 month to dry the surface soils and then implemented an extreme heatwave treatment of 4 consecutive days with air temperatures exceeding 43°C, while monitoring whole‐canopy exchange of CO 2 and H 2 O, leaf temperatures, leaf thermal tolerance, and leaf and branch hydraulic status. The heatwave reduced midday canopy photosynthesis to near zero but transpiration persisted, maintaining canopy cooling. A standard photosynthetic model was unable to capture the observed decoupling between photosynthesis and transpiration at high temperatures, suggesting that climate models may underestimate a moderating feedback of vegetation on heatwave intensity. The heatwave also triggered a rapid increase in leaf thermal tolerance, such that leaf temperatures observed during the heatwave were maintained within the thermal limits of leaf function. All responses were equivalent for trees with a prior history of ambient and warmed (+3°C) temperatures, indicating that climate warming conferred no added tolerance of heatwaves expected in the future. This coordinated physiological response utilizing latent cooling and adjustment of thermal thresholds has implications for tree tolerance of future climate extremes as well as model predictions of future heatwave intensity at landscape and global scales.

A common thermal niche among geographically diverse populations of the widely distributed tree species Eucalyptus tereticornis : No evidence for adaptation to climate‐of‐origin - John E. Drake; Angelica Vårhammar; Dushan Kumarathunge; Belinda E. Medlyn; Sebastian Pfautsch; Peter B. Reich; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2017)
Impacts of climate warming depend on the degree to which plants are constrained by adaptation to their climate‐of‐origin or exhibit broad climatic suitability. We grew cool‐origin, central and warm‐origin provenances of Eucalyptus tereticornis in an array of common temperature environments from 18 to 35.5°C to determine if this widely distributed tree species consists of geographically contrasting provenances with differentiated and narrow thermal niches, or if provenances share a common thermal niche. The temperature responses of photosynthesis, respiration, and growth were equivalent across the three provenances, reflecting a common thermal niche despite a 2,200 km geographic distance and 13°C difference in mean annual temperature at seed origin. The temperature dependence of growth was primarily mediated by changes in leaf area per unit plant mass, photosynthesis, and whole‐plant respiration. Thermal acclimation of leaf, stem, and root respiration moderated the increase in respiration with temperature, but acclimation was constrained at high temperatures. We conclude that this species consists of provenances that are not differentiated in their thermal responses, thus rejecting our hypothesis of adaptation to climate‐of‐origin and suggesting a shared thermal niche. In addition, growth declines with warming above the temperature optima were driven by reductions in whole‐plant leaf area and increased respiratory carbon losses. The impacts of climate warming will nonetheless vary across the geographic range of this and other such species, depending primarily on each provenance's climate position on the temperature response curves for photosynthesis, respiration, and growth.

The carbon fertilization effect over a century of anthropogenic CO 2 emissions: higher intracellular CO 2 and more drought resistance among invasive and native grass species contrasts with increased water use efficiency for woody plants in the US Southwest - Brandon L. Drake; David T. Hanson; Timothy K. Lowrey; Zachary D. Sharp (Global Change Biology, 2017)
From 1890 to 2015, anthropogenic carbon dioxide emissions have increased atmospheric CO 2 concentrations from 270 to 400 mol mol −1 . The effect of increased carbon emissions on plant growth and reproduction has been the subject of study of free‐air CO 2 enrichment ( FACE ) experiments. These experiments have found (i) an increase in internal CO 2 partial pressure ( c i ) alongside acclimation of photosynthetic capacity, (ii) variable decreases in stomatal conductance, and (iii) that increases in yield do not increase commensurate with CO 2 concentrations. Our data set, which includes a 115‐year‐long selection of grasses collected in New Mexico since 1892, is consistent with an increased c i as a response to historical CO 2 increase in the atmosphere, with invasive species showing the largest increase. Comparison with Palmer Drought Sensitivity Index ( PDSI ) for New Mexico indicates a moderate correlation with Δ 13 C ( r 2 = 0.32, P r 2 = 0.00, P = 0.91) after 1950. These results indicate that increased c i may have conferred some drought resistance to these grasses through increased availability of CO 2 in the event of reduced stomatal conductance in response to short‐term water shortage. Comparison with C 3 trees from arid environments ( Pinus longaeva and Pinus edulis in the US Southwest) as well as from wetter environments ( Bromus and Poa grasses in New Mexico) suggests differing responses based on environment; arid environments in New Mexico see increased intrinsic water use efficiency ( WUE ) in response to historic elevated CO 2 while wetter environments see increased c i . This study suggests that (i) the observed increases in c i in FACE experiments are consistent with historical CO 2 increases and (ii) the CO 2 increase influences plant sensitivity to water shortage, through either increased WUE or c i in arid and wet environments, respectively.

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

High-mobility group box 1 in multiple sclerosis - Zohara Sternberg; Daniel Sternberg; Trevor Chichelli; Allison Drake; Neel Patel; Chana Kolb; Kailash Chadha; Jinhee Yu; David Hojnacki (Immunologic Research, 2016)

Short‐term carbon cycling responses of a mature eucalypt woodland to gradual stepwise enrichment of atmospheric CO 2 concentration - John E. Drake; Catriona A. Macdonald; Mark G. Tjoelker; Kristine Y. Crous; Teresa E. Gimeno; Brajesh K. Singh; Peter B. Reich; Ian C. Anderson; David S. Ellsworth (Global Change Biology, 2016)
Projections of future climate are highly sensitive to uncertainties regarding carbon (C) uptake and storage by terrestrial ecosystems. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment was established to study the effects of elevated atmospheric CO 2 concentrations (eCO 2 ) on a native mature eucalypt woodland with low fertility soils in southeast Australia. In contrast to other FACE experiments, the concentration of CO 2 at Euc FACE was increased gradually in steps above ambient (+0, 30, 60, 90, 120, and 150 ppm CO 2 above ambient of ~400 ppm), with each step lasting approximately 5 weeks. This provided a unique opportunity to study the short‐term (weeks to months) response of C cycle flux components to eCO 2 across a range of CO 2 concentrations in an intact ecosystem. Soil CO 2 efflux (i.e., soil respiration or R soil ) increased in response to initial enrichment (e.g., +30 and +60 ppm CO 2 ) but did not continue to increase as the CO 2 enrichment was stepped up to higher concentrations. Light‐saturated photosynthesis of canopy leaves ( A sat ) also showed similar stimulation by elevated CO 2 at +60 ppm as at +150 ppm CO 2 . The lack of significant effects of eCO 2 on soil moisture, microbial biomass, or activity suggests that the increase in R soil likely reflected increased root and rhizosphere respiration rather than increased microbial decomposition of soil organic matter. This rapid increase in R soil suggests that under eCO 2, additional photosynthate was produced, transported belowground, and respired. The consequences of this increased belowground activity and whether it is sustained through time in mature ecosystems under eCO 2 are a priority for future research.

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species - John E. Drake; Michael J. Aspinwall; Sebastian Pfautsch; Paul D. Rymer; Peter B. Reich; Renee A. Smith; Kristine Y. Crous; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2015)
As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate‐shift experiment in widely distributed Eucalyptus tereticornis and E. grandis using provenances originating along a ~2500 km latitudinal transect (15.5–38.0°S) in eastern Australia. We grew 21 provenances in conditions approximating summer temperatures at seed origin and warmed temperatures (+3.5 °C) using a series of climate‐controlled glasshouse bays. The effects of +3.5 °C warming strongly depended on home climate. Cool‐origin provenances responded to warming through an increase in photosynthetic capacity and total leaf area, leading to enhanced growth of 20–60%. Warm‐origin provenances, however, responded to warming through a reduction in photosynthetic capacity and total leaf area, leading to reduced growth of approximately 10%. These results suggest that there is predictable intraspecific variation in the capacity of trees to respond to warming; cool‐origin taxa are likely to benefit from warming, while warm‐origin taxa may be negatively affected.

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Winter habitat use does not influence spring arrival dates or the reproductive success of Yellow Warblers breeding in the arctic - Anna Drake; Michaela Martin; David J. Green (Polar Biology, 2014)

Dispersal limitation, speciation, environmental filtering and niche differentiation influence forest tree communities in West Polynesia - Janet Franklin; Gunnar Keppel; Edward L. Webb; Joshua O. Seamon; Sergio J. Rey; David W. Steadman; Susan K. Wiser; Donald R. Drake (Journal of Biogeography, 2013)
Aim Regional patterns of forest composition in West Polynesia were analysed to determine the relative importance of dispersal limitation, speciation, environmental filtering and biotic interactions. Location West Polynesia (Fiji, Tonga, Samoa). Methods We applied clustering and indicator species analysis to presence/absence data for 397 tree taxa in 338 forest plots to detect groups of plots sharing similar species composition. Patterns of plot composition and co‐occurrence of congeneric species were compared between archipelagos for evidence of dispersal limitation, speciation, and environmental filtering versus competitive displacement or niche differentiation across the three archipelagos at the local (plot) and regional scales. Results Dispersal limitation was evident in the compositional segregation of inland rain forests across the three archipelagos, whereas compositional overlap was widespread for coastal forests, which are composed of species dispersed by water. Within genera, species numbers attenuated from Fiji to Tonga to Samoa, but speciation also contributed to compositional differences in all three island groups. Environmental filtering was suggested by the distinct composition of both secondary and mature inland rain forest versus coastal forest. At the local scale, however, clumping of congeners, which might suggest fine‐scale environmental filtering, was observed for only a minority of inland forest genera. Most genera showed either overdispersion, suggesting competitive displacement or niche differentiation, or patterns not significantly different from random. Main conclusions Well‐established biogeographical patterns of dispersal limitation and speciation contribute to West Polynesian tree diversity at the community scale. Environmental filtering and competitive displacement further structure forest communities; the evidence from this study suggests that environmental filtering is more important at a landscape scale, while competitive displacement may be more important at a local scale, although their relative importance varies considerably among taxa.

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

Comparison of techniques used to count single-celled viable phytoplankton - Mia K. Steinberg; Matthew R. First; Edward J. Lemieux; Lisa A. Drake; Bruce N. Nelson; David M. Kulis; Donald M. Anderson; Nicholas A. Welschmeyer; Penny R. Herring (Journal of Applied Phycology, 2012)

Recombinant human hyaluronidase PH20 (rHuPH20) facilitates subcutaneous infusions of large volumes of immunoglobulin in a swine model - David W. Kang; Laurence Jadin; Tara Nekoroski; Fred H. Drake; Monica L. Zepeda (Drug Delivery and Translational Research, 2012)

Conservation status of eulachon in the California Current - Richard G Gustafson; Michael J Ford; Peter B Adams; Jonathan S Drake; Robert L Emmett; Kurt L Fresh; Mindy Rowse; Elizabeth A K Spangler; Robert E Spangler; David J Teel; Matthew T Wilson (Fish and Fisheries, 2012)
Eulachon ( Thaleichthys pacificus ), an anadromous smelt in the Northeast Pacific Ocean was examined for listing under the USA’s Endangered Species Act (ESA). A southern Distinct Population Segment (DPS) of eulachon – that occurs in the California Current and is composed of numerous subpopulations that spawn in rivers from northern California to northern British Columbia – was identified on the basis of ecological and environmental characteristics, and to a lesser extent, genetic and life history variation. Although the northern terrestrial boundary of this DPS remains uncertain, our consensus opinion was that this northern boundary occurs south of the Nass River and that the DPS was discrete from more northern eulachon, as well as significant to the biological species as a whole and thus is a ‘species’ under the ESA. Eulachon have been nearly absent in northern California for over two decades, have declined in the Fraser River by over 97% in the past 10 years, and are at historically low levels in other British Columbia rivers in the DPS, and nearly so in the Columbia River. Major threats to southern eulachon include climate change impacts on ocean and freshwater habitat, by‐catch in offshore shrimp trawl fisheries, changes in downstream flow timing and intensity owing to dams and water diversions, and predation. These threats, together with large declines in abundance, indicate that the southern DPS of eulachon is at moderate risk of extinction throughout all of its range. The southern DPS was listed as threatened under the ESA in May 2010 – the first marine forage fish to be afforded these statutory protections, which apply only to waters under U.S. jurisdiction.

Shallow coastal lakes in New Zealand: current conditions, catchment-scale human disturbance, and determination of ecological integrity - D. C. Drake; David Kelly; Marc Schallenberg (Hydrobiologia, 2011)

Effect of Serum on Transfection by Polyethylenimine/Virus-Like Particle Hybrid Gene Delivery Vectors - David M. Drake; Rahul K. Keswani; Daniel W. Pack (Pharmaceutical Research, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

Potential health impacts of heavy-metal exposure at the Tar Creek Superfund site, Ottawa County, Oklahoma - John S. Neuberger; Stephen C. Hu; K. David Drake; Rebecca Jim (Environmental Geochemistry and Health, 2009)

Disturbance, rainfall and contrasting species responses mediated aboveground biomass response to 11 years of CO 2 enrichment in a Florida scrub‐oak ecosystem - TROY J. SEILER; DANIEL P. RASSE; JIAHONG LI; PAUL DIJKSTRA; HANS P. ANDERSON; DAVID P. JOHNSON; THOMAS L. POWELL; BRUCE A. HUNGATE; C. ROSS HINKLE; BERT G. DRAKE (Global Change Biology, 2009)
This study reports the aboveground biomass response of a fire‐regenerated Florida scrub‐oak ecosystem exposed to elevated CO 2 (1996–2007), from emergence after fire through canopy closure. Eleven years exposure to elevated CO 2 caused a 67% increase in aboveground shoot biomass. Growth stimulation was sustained throughout the experiment; although there was significant variability between years. The absolute stimulation of aboveground biomass generally declined over time, reflecting increasing environmental limitations to long‐term growth response. Extensive defoliation caused by hurricanes in September 2004 was followed by a strong increase in shoot density in 2005 that may have resulted from reopening the canopy and relocating nitrogen from leaves to the nutrient‐poor soil. Biomass response to elevated CO 2 was driven primarily by stimulation of growth of the dominant species, Quercus myrtifolia , while Quercus geminata , the other co‐dominant oak, displayed no significant CO 2 response. Aboveground growth also displayed interannual variation, which was correlated with total annual rainfall. The rainfall × CO 2 interaction was partially masked at the community level by species‐specific responses: elevated CO 2 had an ameliorating effect on Q. myrtifolia growth under water stress. The results of this long‐term study not only show that atmospheric CO 2 concentration had a consistent stimulating effect on aboveground biomass production, but also showed that available water is the primary driver of interannual variation in shoot growth and that the long‐term response to elevated CO 2 may have been caused by other factors such as nutrient limitation and disturbance.

Cocaine self-administration on a hold-down schedule of reinforcement in rats - Drake Morgan; Yu Liu; Erik B. Oleson; David C. S. Roberts (Psychopharmacology, 2009)

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

Parent–offspring resource allocation in domestic pigs - Anna Drake; David Fraser; Daniel M. Weary (Behavioral Ecology and Sociobiology, 2008)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Cross-sensitization of the reinforcing effects of cocaine and amphetamine in rats - Yu Liu; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2007)

Impacts of Hurricane Frances on Florida scrub‐oak ecosystem processes: defoliation, net CO 2 exchange and interactions with elevated CO 2 - JIAHONG LI; THOMAS L. POWELL; TROY J. SEILER; DAVID P. JOHNSON; HANS P. ANDERSON; ROSVEL BRACHO; BRUCE A. HUNGATE; CHARLES R. HINKLE; BERT G. DRAKE (Global Change Biology, 2007)
Hurricane disturbances have profound impacts on ecosystem structure and function, yet their effects on ecosystem CO 2 exchange have not been reported. In September 2004, our research site on a fire‐regenerated scrub‐oak ecosystem in central Florida was struck by Hurricane Frances with sustained winds of 113 km h −1 and wind gusts as high as 152 km h −1 . We quantified the hurricane damage on this ecosystem resulting from defoliation: we measured net ecosystem CO 2 exchange, the damage and recovery of leaf area, and determined whether growth in elevated carbon dioxide concentration in the atmosphere ( C a ) altered this disturbance. The hurricane decreased leaf area index (LAI) by 21%, which was equal to 60% of seasonal variation in canopy growth during the previous 3 years, but stem damage was negligible. The reduction in LAI led to a 22% decline in gross primary production (GPP) and a 25% decline in ecosystem respiration ( R e ). The compensatory declines in GPP and R e resulted in no significant change in net ecosystem production (NEP). Refoliation began within a month after the hurricane, although this period was out of phase with the regular foliation period, and recovered 20% of the defoliation loss within 2.5 months. Full recovery of LAI, ecosystem CO 2 assimilation, and ecosystem respiration did not occur until the next growing season. Plants exposed to elevated C a did not sustain greater damage, nor did they recover faster than plants grown under ambient C a . Thus, our results indicate that hurricanes capable of causing significant defoliation with negligible damage to stems have negligible effects on NEP under current or future CO 2 ‐enriched environment.

Fecundity as a Basis for Risk Assessment of Nonindigenous Freshwater Molluscs - REUBEN P. KELLER; JOHN M. DRAKE; DAVID M. LODGE (Conservation Biology, 2007)
The most efficient way to reduce future damages from nonindigenous species is to prevent the introduction of harmful species. Although ecologists have long sought to predict the identity of such species, recent methodological advances promise success where previous attempts failed. We applied recently developed risk assessment approaches to nonindigenous freshwater molluscs at two geographic scales: the Laurentian Great Lakes basin and the 48 contiguous states of the United States. We used data on natural history and biogeography to discriminate between established freshwater molluscs that are benign and those that constitute nuisances (i.e., cause environmental and/or economic damage). Two statistical techniques, logistic regression and categorical tree analysis, showed that nuisance status was positively associated with fecundity. Other aspects of natural history and biogeography did not significantly affect likelihood of becoming a nuisance. We then used the derived statistical models to predict the chance that 15 mollusc species not yet in natural ecosystems would cause damage if they become established. We also tested whether time since establishment is related to the likelihood that nonindigenous mollusc species in the Great Lakes and United States would cause negative impacts. No significant relationship was evident at the U.S. scale, but recently established molluscs within the Great Lakes were more likely to cause negative impacts. This may reflect changing environmental conditions, changing patterns of trade, or may be an indication of “invasional meltdown.” Our quantitative analyses could be extended to other taxa and ecosystems and offer a number of improvements over the qualitative risk assessments currently used by U.S. (and other) government agencies.

Multiple Exposures to Chlorhexidine and Xylitol: Adhesion and Biofilm Formation by Streptococcus mutans - Adriana Modesto; David R. Drake (Current Microbiology, 2006)

Demographic Stochasticity, Environmental Variability, and Windows of Invasion Risk for Bythotrephes Longimanus in North America - John M. Drake; Kevin L. S. Drury; David M. Lodge; Agnes Blukacz; N. D. Yan; Greg Dwyer (Biological Invasions, 2006)

Discrete-trials heroin self-administration produces sensitization to the reinforcing effects of cocaine in rats - Sara J. Ward; Christopher Läck; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2006)

Allee Effects, Propagule Pressure and the Probability of Establishment: Risk Analysis for Biological Invasions - John M. Drake; David M. Lodge (Biological Invasions, 2006)

Effects of extended-access self-administration and deprivation on breakpoints maintained by cocaine in rats - Yu Liu; David C. S. Roberts; Drake Morgan (Psychopharmacology, 2005)

Binge self-administration and deprivation produces sensitization to the reinforcing effects of cocaine in rats - Drake Morgan; Mark A. Smith; David C. S. Roberts (Psychopharmacology, 2005)

Invasion in space and time: non‐native species richness and relative abundance respond to interannual variation in productivity and diversity - Elsa E. Cleland; Melinda D. Smith; Sandy J. Andelman; Christy Bowles; Karen M. Carney; M. Claire Horner‐Devine; John M. Drake; Sarah M. Emery; Joel M. Gramling; David B. Vandermast (Ecology Letters, 2004)
Ecologists have long sought to understand the relationships among species diversity, community productivity and invasion by non‐native species. Here, four long‐term observational datasets were analyzed using repeated measures statistics to determine how plant species richness and community resource capture (i.e. productivity) influenced invasion. Multiple factors influenced the results, including the metric used to quantify invasion, interannual variation and spatial scale. Native richness was positively correlated with non‐native richness, but was usually negatively correlated with non‐native abundance, and these patterns were stronger at the larger spatial scale. Logistic regressions indicated that the probability of invasion was reduced both within and following years with high productivity, except at the desert grassland site where high productivity was associated with increased invasion. Our analysis suggests that while non‐natives were most likely to establish in species rich communities, their success was diminished by high resource capture by the resident community.

Effects of positive allosteric modulators of the GABA B receptor on cocaine self-administration in rats - Mark A. Smith; David L. Yancey; Drake Morgan; Yu Liu; Wolfgang Froestl; David C. S. Roberts (Psychopharmacology, 2004)

Effects of environmental variation on extinction and establishment - John M. Drake; David M. Lodge (Ecology Letters, 2004)
Theoretical models predict that increasing environmental variation increases the probability of extinction, decreases the probability of establishment, and influences the distribution of times to extinction or establishment. We conducted an experiment with 281 independent populations of Daphnia magna under controlled laboratory conditions to test these predictions. Consistent with the theory, the fraction of populations going extinct increased and the fraction of populations establishing self‐sustaining populations decreased under higher levels of environmental variation compared with controls. Time to extinction decreased under higher levels of environmental variation, but we found no effect on time to establishment. These results are consistent with theoretical predictions from models of extinction. They therefore support the use of stochastic population models to predict the fates of introductions of non‐indigenous species or native endangered species based on historic fluctuations and/or expected future conditions.

Effects of elevated atmospheric CO 2 on net ecosystem CO 2 exchange of a scrub–oak ecosystem - Graham J. Hymus; David P. Johnson; Sabina Dore; Hans P. Anderson; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2003)
We report the results of a 2‐year study of effects of the elevated (current ambient plus 350 μmol CO 2 mol −1 ) atmospheric CO 2 concentration ( C a ) on net ecosystem CO 2 exchange ( NEE ) of a scrub–oak ecosystem. The measurements were made in open‐top chambers (OTCs) modified to function as open gas‐exchange systems. The OTCs enclosed samples of the ecosystem (ca. 10 m 2 surface area) that had regenerated after a fire, 5 years before, in either current ambient or elevated C a . Throughout the study, elevated C a increased maximum NEE ( NEE max ) and the apparent quantum yield of the NEE ( φ NEE ) during the photoperiod. The magnitude of the stimulation of NEE max , expressed per unit ground area, was seasonal, rising from 50% in the winter to 180% in the summer. The key to this stimulation was effects of elevated C a , and their interaction with the seasonal changes in the environment, on ecosystem leaf area index, photosynthesis and respiration. The separation of these factors was difficult. When expressed per unit leaf area the stimulation of the NEE max ranged from 7% to 60%, with the increase being dependent on increasing soil water content ( W soil ). At night, the CO 2 effluxes from the ecosystem ( NEE night ) were on an average 39% higher in elevated C a . However, the increase varied between 6% and 64%, and had no clear seasonality. The partitioning of NEE night into its belowground ( R below ) and aboveground ( R above ) components was carried out in the winter only. A 35% and 27% stimulation of NEE night in December 1999 and 2000, respectively, was largely due to a 26% and 28% stimulation of R below in the respective periods, because R below constituted ca. 87% of NEE night . The 37% and 42% stimulation of R above in December 1999 and 2000, respectively, was less than the 65% and 80% stimulation of the aboveground biomass by elevated C a at these times. An increase in the relative amount of the aboveground biomass in woody tissue, combined with a decrease in the specific rate of stem respiration of the dominant species Quercus myrtifolia in elevated C a , was responsible for this effect. Throughout this study, elevated C a had a greater effect on carbon uptake than on carbon loss, in terms of both the absolute flux and relative stimulation. Consequently, for this scrub–oak ecosystem carbon sequestration was greater in the elevated C a during this 2‐year study period.

Acidovorax ‐like symbionts in the nephridia of earthworms - Andreas Schramm; Seana K. Davidson; Jeremy A. Dodsworth; Harold L. Drake; David A. Stahl; Nicole Dubilier (Environmental Microbiology, 2003)
Summary Dense accumulations of bacteria in the excretory organs, nephridia, were first described more than 75 years ago in members of the annelid family Lumbricidae (earthworms). These nephridial symbionts were assumed to play a role in the degradation of proteins in the excretory fluid for nitrogen recycling. In the present study, the phylogenetic affiliation of the nephridial bacteria of the earthworms Lumbricus terrestris , Aporrectodea tuberculata , Octolasion lacteum and Eisenia foetida was resolved. The 16S rRNA gene sequences of the symbionts formed a monophyletic cluster within the genus Acidovorax . Similarity between symbiont sequences from different host species was 95.5–97.6%, whereas similarity was> 99% between symbiont sequences from individuals of the same species. Densely packed bacteria were detected in the ampulla of the nephridia by fluorescence in situ hybridization (FISH) using Acidovorax ‐specific oligonucleotide probes. No other bacterial cells could be found by FISH, although a few sequences other than Acidovorax had been found by PCR and cloning. These results suggest that the Acidovorax‐ earthworm symbiosis is a stable, host‐specific association that has evolved from a common bacterial ancestor. Given the close phylogenetic relationship of the symbionts to proteolytic, free‐living Acidovorax species, they may indeed play a role in protein degradation during nitrogen excretion by earthworms.

Above‐ground biomass estimation in closed canopy Neotropical forests using lidar remote sensing: factors affecting the generality of relationships - Jason B. Drake; Robert G. Knox; Ralph O. Dubayah; David B. Clark; Richard Condit; J. Bryan Blair; Michelle Hofton (Global Ecology and Biogeography, 2003)
Aim Previous studies have developed strong, site‐specific relationships between canopy metrics from lidar (light detecting and ranging) remote sensing data and forest structural characteristics such as above‐ground biomass (AGBM), but the generality of these relationships is unknown. In this study, we examine the generality of relationships between lidar metrics and forest structural characteristics, including AGBM, from two study areas in Central America with different precipitation patterns. Location A series of tropical moist forest sites in Panama and a tropical wet forest in Costa Rica. Methods Canopy metrics (e.g. canopy height) were calculated from airborne lidar data. Basal area, mean stem diameter and AGBM were calculated from measurements taken as a part of ongoing forest dynamics studies in both areas. We examined the generality of relationship between lidar metrics and forest structure, and possible environmental effects (e.g. leaf phenology). Results We found that lidar metrics were strongly correlated ( R 2 : 0.65–0.92) with mean stem diameter, basal area and AGBM in both regions. We also show that the relationships differed between these regions. Deciduousness of canopy trees in the tropical moist forest area accounted for the differences in predictive equations for stem diameter and basal area. The relationships between lidar metrics and AGBM, however, remained significantly different between the two study areas even after adjusting for leaf drop. We attribute this to significant differences in the underlying allometric relationships between stem diameter and AGBM in tropical wet and moist forests. Conclusions Important forest structural characteristics can be estimated reliably across a variety of conditions sampled in these closed‐canopy tropical forests. Environmental factors such as drought deciduousness have an important influence on these relationships. Future efforts should continue to examine climatic factors that may influence the generality of the relationships between lidar metrics and forest structural characteristics and assess more rigorously the generality of field‐derived allometric relationships.

Cross validation of open‐top chamber and eddy covariance measurements of ecosystem CO 2 exchange in a Florida scrub‐oak ecosystem - Sabina Dore; Graham J. Hymus; David P. Johnson; C. R. Hinkle; Riccardo Valentini; Bert G. Drake (Global Change Biology, 2003)
Simultaneous measurements of net ecosystem CO 2 exchange (NEE) were made in a Florida scrub‐oak ecosystem in August 1997 and then every month between April 2000 to July 2001, using open top chambers (NEE O ) and eddy covariance (NEE E ). This study provided a cross validation of these two different techniques for measuring NEE. Unique characteristics of the comparison were that the measurements were made simultaneously, in the same stand, with large replicated chambers enclosing a representative portion of the ecosystem (75 m 2 , compared to approximately 1–2 ha measured by the eddy covariance system). The value of the comparison was greatest at night, when the microclimate was minimally affected by the chambers. For six of the 12 measurement periods, night NEE O was not significantly different to night NEE E , and for the other periods the maximum difference was 1.1 µ mol m − 2 s − 1 , with an average of 0.72 ± 0.09 µ mol m − 2 s − 1 . The comparison was more difficult during the photoperiod, because of differences between the microclimate inside and outside the chambers. During the photoperiod, air temperature (T air ) and air vapour pressure deficits (VPD) became progressively higher inside the chambers until mid‐afternoon. In the morning NEE O was higher than NEE E by about 26%, consistent with increased temperature inside the chambers. Over the mid‐day period and the afternoon, NEE O was 8% higher that NEE E , regardless of the large differences in microclimate. This study demonstrates both the uses and difficulties associated with attempting to cross validate NEE measurements made in chambers and using eddy covariance. The exercise was most useful at night when the chamber had a minimal effect on microclimate, and when the measurement of NEE is most difficult.

The biology of insularity: an introduction - Donald R. Drake; Christa P. H. Mulder; David R. Towns; Charles H. Daugherty (Journal of Biogeography, 2002)
Insular environments, ranging from oceanic islands to fragments of once‐contiguous natural systems, have long been used by biologists to test basic principles of ecology, evolution and biogeography. More recently, insular environments have figured prominently in conservation ecology, where the aim has usually been to conserve species or assemblages unique to isolated habitats. Improving the level of communication among the evolutionary biologists, theoretical ecologists and conservation biologists who study insular biotas will work to the benefit of all. This volume was inspired by a recent conference on the ecology of insular biotas, in which participants from a wide range of disciplines came together to compare ecological processes across a variety of taxonomic groups inhabiting a wide range of isolated environments. In this introduction, we point out the themes underlying these very diverse contributions. First we elaborate on the value of islands for elucidating processes underlying ecosystem functioning, population dynamics of reintroduced species, and restoration of disturbed habitats, and emphasize those areas where the use of islands could be expanded. The second section focuses on the link between ecology and evolutionary processes in insular systems and includes examples from oceanic islands, naturally patchy habitats and recently fragmented habitats. The third section illustrates some of the ways that invasive alien species on oceanic islands affect plant–animal mutualisms, particularly seed dispersal and pollination. The final section, on consequences of habitat fragmentation, focuses mainly on studies that describe the consequences that fragmentation has for plants and animals as they are forced into artificially insular environments. We close with a study that points out the differences among types of insular systems and identifies gaps in our knowledge of insular biotas, particularly the importance of explicitly incorporating patch type, age and patch–matrix contrasts in research. Finally, we recommend a greater emphasis on linking ecological theory and applied research, and improving communication between those who ask basic ecological questions and those who use insular systems for conservation.

Acclimation of photosynthesis and respiration to elevated atmospheric CO 2 in two Scrub Oaks - Graham J. Hymus; Tom G. Snead; David P. Johnson; Bruce A. Hungate; Bert G. Drake (Global Change Biology, 2002)
For two species of oak, we determined whether increasing atmospheric CO 2 concentration ( C a ) would decrease leaf mitochondrial respiration (R) directly, or indirectly owing to their growth in elevated C a , or both. In particular, we tested whether acclimatory decreases in leaf‐Rubisco content in elevated C a would decrease R associated with its maintenance. This hypothesis was tested in summer 2000 on sun and shade leaves of Quercus myrtifolia Willd. and Quercus geminata Small. We also measured R on five occasions between summer 1999 and 2000 on leaves of Q. myrtifolia . The oaks were grown in the field for 4 years, in either current ambient or elevated (current ambient + 350 µmol mol −1 ) C a , in open‐top chambers (OTCs). For Q. myrtifolia , an increase in C a from 360 to 710 µmol mol −1 had no direct effect on R at any time during the year. In April 1999, R in young Q. myrtifolia leaves was significantly higher in elevated C a —the only evidence for an indirect effect of growth in elevated C a . Leaf R was significantly correlated with leaf nitrogen (N) concentration for the sun and shade leaves of both the species of oak. Acclimation of photosynthesis in elevated C a significantly reduced maximum RuBP‐saturated carboxylation capacity ( V c max ) for both the sun and shade leaves of only Q. geminata . However, we estimated that only 11–12% of total leaf N was invested in Rubisco; consequently, acclimation in this plant resulted in a small effect on N and an insignificant effect on R. In this study measurements of respiration and photosynthesis were made on material removed from the field; this procedure had no effect on gas exchange properties. The findings of this study were applicable to R expressed either per unit leaf area or unit dry weight, and did not support the hypothesis that elevated C a decreases R directly, or indirectly owing to acclimatory decreases in Rubisco content.

Elevated atmospheric CO 2 stimulates aboveground biomass in a fire‐regenerated scrub‐oak ecosystem - Paul Dijkstra; Graham Hymus; Debra Colavito; David A. Vieglais; Christina M. Cundari; David P. Johnson; Bruce A. Hungate; C. ROSS Hinkle; Bert G. Drake (Global Change Biology, 2002)
The effect of elevated atmospheric CO 2 concentration ( C a ) on the aboveground biomass of three oak species, Quercus myrtifolia , Q. geminata , and Q. chapmanii , was estimated nondestructively using allometric relationships between stem diameter and aboveground biomass after four years of experimental treatment in a naturally fire‐regenerated scrub‐oak ecosystem. After burning a stand of scrub‐oak vegetation, re‐growing plants were exposed to either current ambient (379 µL L −1 CO 2 ) or elevated (704 µL L −1 CO 2 ) C a in 16 open‐top chambers over a four‐year period, and measurements of stem diameter were carried out annually on all oak shoots within each chamber. Elevated C a significantly increased aboveground biomass, expressed either per unit ground area or per shoot; elevated C a had no effect on shoot density. The relative effect of elevated C a on aboveground biomass increased each year of the study from 44% (May 96–Jan 97), to 55% (Jan 97–Jan 98), 66% (Jan 98–Jan 99), and 75% (Jan 99–Jan 00). The effect of elevated C a was species specific: elevated C a significantly increased aboveground biomass of the dominant species, Q. myrtifolia , and tended to increase aboveground biomass of Q. chapmanii , but had no effect on aboveground biomass of the subdominant, Q. geminata . These results show that rising atmospheric CO 2 has the potential to stimulate aboveground biomass production in ecosystems dominated by woody species, and that species‐specific growth responses could, in the long term, alter the composition of the scrub‐oak community.

Impact of Human Activity on Regional Forest Composition and Dynamics in Central New England - Janice L. Fuller; David R. Foster; Jason S. McLachlan; Natalie Drake (Ecosystems, 1998)

The Anatomy of an Oceanic Flood Deposit - Robert Wheatcroft; Jeffry Borgeld; Rebecca Born; David Drake; Elana Leithold; Charles Nittrouer; Cristopher Sommerfield (Oceanography, 1996)

Distribution and Characteristics of Suspended Sediment on the Amazon Shelf - Gail Kineke; Richard Sternberg; David Cacchione; Kate Kranck; David Drake (Oceanography, 1991)